2017
DOI: 10.1038/pr.2017.16
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to bisphenols and phthalates and association with oxidant stress, insulin resistance, and endothelial dysfunction in children

Abstract: Background The health effects of bisphenol A (BPA) and di-(2-ethylhexyl) phthalate (DEHP) have been studied extensively in children. The impact of other chemicals in these two classes has not been investigated as fully. Methods We conducted a cross-sectional pilot study of 10–13 year old healthy children. We assessed descriptive, univariable and multivariable associations of urinary metabolites of bisphenols and phthalates with oxidant stress, insulin resistance, body mass, and endothelial dysfunction. Possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(63 citation statements)
references
References 42 publications
4
58
1
Order By: Relevance
“…The last article from 2017 was an observational study of children aged between 10 and 13 years. They found that urinary BPS levels were significantly correlated with insulin resistance, albuminuria, and irregular vascular function [39]. Finally, the single article from 2019 is an excellent large scale clinical/observational study from China.…”
Section: Dietary Bps Exposure and Obesogenic Effects/metabolic Disordersmentioning
confidence: 99%
“…The last article from 2017 was an observational study of children aged between 10 and 13 years. They found that urinary BPS levels were significantly correlated with insulin resistance, albuminuria, and irregular vascular function [39]. Finally, the single article from 2019 is an excellent large scale clinical/observational study from China.…”
Section: Dietary Bps Exposure and Obesogenic Effects/metabolic Disordersmentioning
confidence: 99%
“…Finally, patients on hemodialysis are regularly exposed to considerable amounts of phthalates leaching by plastic tubing (Faouzi et al, 1999). Although the field is aware of the associated risks, the probable contribution of phthalates on comorbidities (Kataria et al, 2017) and extracellular vesiculation [extensively studied in stored blood (Serrano et al, 2016)], as well as their probable dissemination to sensitive targets through EVs, have not been investigated so far in CKD.…”
Section: Evs In the Plasma Of Ckd Patients: General Outline Of Our Knmentioning
confidence: 99%
“…Utilizing a mouse model, we reported that BPA or DEHP alters testicular development in newborns and spermatogenesis in adult animals . The exposure of BPA and DEHP leads to oxidative stress in cells and has been recently associated with epigenetic changes . In particular, BPA alters global DNA and H3 histone methylation in human cell lines, and causes DNA hydroxymethylation, partially dependent on trimethylation of histone H3, during spermatogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The exposure of BPA and DEHP leads to oxidative stress in cells and has been recently associated with epigenetic changes. 23,24 In particular, BPA alters global DNA and H3 histone methylation in human cell lines, 25 and causes DNA hydroxymethylation, partially dependent on trimethylation of histone H3, during spermatogenesis. 26 Similarly, in the mouse, pubertal exposure to DEHP resulted in defects in spermatogenesis attributed to the inhibition of G9amediated histone methylation.…”
Section: Introductionmentioning
confidence: 99%